2008
DOI: 10.1243/09544062jmes1296
|View full text |Cite
|
Sign up to set email alerts
|

Damage localization in hydraulic turbine blades using kernel-independent component analysis and support vector machines

Abstract: A hydraulic turbine runner has a complex structure, and traditional source location methods do not have the higher accuracy to meet engineering requirements. The source location of crack acoustic emission (AE) signals in hydraulic turbine blades has been researched by combining it with kernel-independent component analysis (KICA) as feature extraction, with support vector machines (SVMs) as position recognition. This method is compared with those applied SVMs with feature extraction using kernel principal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Thus, the support vector machine (SVM) was used. Wang et al 16 used SVM to locate crack of turbine runners. The result shows that the recognition rate in the crack region is good with small samples.…”
Section: Aementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the support vector machine (SVM) was used. Wang et al 16 used SVM to locate crack of turbine runners. The result shows that the recognition rate in the crack region is good with small samples.…”
Section: Aementioning
confidence: 99%
“…[16], the different methods and different number of samples were used to solve the damage localization in turbine blades. The motivation of this research is to verify the validity of crack location based on KICA and WNN and to find out which is more suitable for the large-size complex structure with a large input dimensions and output patterns the large number of samples were used in this study.…”
Section: Aementioning
confidence: 99%
“…The work by Wang et al. in [14] and Samanta et al. in [4] concluded that the prediction performance using the essential AE parameters (i.e.…”
Section: Three‐dimensional Location Experiments Of Ae Sourcesmentioning
confidence: 99%
“…For example, Wang et al. [14] classified major crack regions in a hydraulic turbine blade into three patterns and recognised regions of AE sources by SVM. However up to now, in these situations, the damage localisation does not represent the real positioning (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the limited human resource of expert personnel restricts a widespread application of the fault diagnosis techniques. As such, in order to help inexperienced operators to quickly make an objective and accurate decision on machinery running conditions, a wide variety of automated classification paradigms have been introduced for fault classification such as expert systems (ESs), fuzzylogic inference [25,26], NNs [6,[27][28][29][30][31][32][33][34][35], and SVMs [36][37][38][39][40]. ESs may be the earliest attempt made to automate fault diagnosis, which documents the expertise of human experts into a computer system and emulates human reasoning process.…”
Section: Introductionmentioning
confidence: 99%